EFFECT OF NATURAL DYES ADDITION OF CATFISH (Pangasius hypophthalmus) WET NOODLES ON CONSUMER ACCEPTANCE - Ridwan, Muhammad; Sari, N. Ira; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of natural dyes addition of catfish wet noodles on consumer acceptance, which was given coloring from beetroots, mustard greens, and carrots. The method used in this research was the experimental method of making catfish wet noodles with the addition of different natural dyes. A non-factorial Completely Randomized Design was used in this research with 4 types of treatment, namely (W0) without natural dyes, (W1) red color from beetroots, (W2) green color from mustard greens, and (W3) orange color from carrots. All treatments were repeated 3 times so that the number of experimental units was 12 units. The parameter measured in this study was the preference test. Based on the results of the study, it was concluded that the catfish wet noodles with the addition of natural dyes from mustard greens (green colour) most preferred by consumers acceptance with 71 panelists (88.7%). The addition of natural dyes in catfish wet noodles was significantly affected to appearance and odor, however, did not significantly affect to texture value and taste value. Based on the parameters tested, the results of organoleptic values of appearance (7.20) which criteria of bright green, odor(6.95) which criteria of mustard greens odor, texture (6.76)which criteria of thick, elastic and slightly sticky, and taste (6.49) which criteria of slightly mustard greens taste. Keywords: Catfish, wet noodles, natural dyes.